KETERAMPILAN TEKNIK DASAR BOLAVOLI PADA KLUB TERUSAN KEMPAS KABUPATEN INDRAGIRI HILIR - Devit Wilastra (Jurnal Olahraga Indragiri, 2018)
This type of research is Descriptive. This study aims to find out how big the "Basic Technique of Bollywood Skills in the Gaung Sub-District Sports Club in the District of Indragiri Hilir". The population in this study is the Kempas Canal Club, amounting to 16 people. The sample was taken using a total sampling technique that is all volleyball extracurricular students totaling 16 people. To find out the ability of basic technical skills, the instruments used in this study were service tests, lower pass tests, upper tide tests, and volleyball smash tests.Based on the results of the research that the writer did at the Kempas Canal Club, it can be concluded that the basic volleyball technical skills of athletes have not been well developed, this is shown by the service test results of 44% in the medium category, the results of pasing tests on 63% of athletes in the medium category, the results lower passive test 38% of athletes in the medium category, and smash test results 50% of athletes in the less category.